Copolymer networks with contorted units and highly polar groups for ultra-fast selective cationic dye adsorption and iodine uptake. (17th January 2022) - Baig, Noorullah; Shetty, Suchetha; Pasha, Sheik Saleem; Pramanik, Sumit Kumar; Alameddine, Bassam
Abstract: Three organic copolymer networks CP1-3 were synthesized using a mild polycondensation reaction of the commercially available tetrafluoroterephthalonitrile with three different building blocks with contorted geometries and bearing two hydroxyl groups, namely, triptycene 1a, fluorescein 1b, and phenolphthalein 1c . The target cross-linked copolymers CP1-3 revealed ultra-fast uptake of the cationic dye methylene blue (MB ) with an adsorption capacity reaching 300 mg/g. In addition, selectivity studies proved the preference of CP2 towards the cationic dye MB over the anionic dyes, such as, methyl orange (MO ) and Congo red (CR ). Copolymers CP1-3 also show superior iodine uptake properties reaching ∼150 wt% with virtually no loss in the adsorption capacity even after several successive adsorption-desorption cycles. The easy preparation and promising dyes adsorption and iodine uptake capacities promote the contorted copolymers CP1-3 as promising materials for environmental remediation applications. Graphical abstract: Image 1 Highlights: Versatile synthesis of three copolymer networks CP1-3 bearing contorted units and polar groups. CP1-3 disclose high thermal stability with a 10% weight loss temperature >385ᵒC. Ultrafast uptake of methylene blue in few minutes with a maximum capacity reaching 300 mg g −1 Selectivity tests show a quantitative preference towards cationic over anionic dyes. Superior iodine adsorption reaching 150 wt% even after several cycles.